A STUDY OF BEHAVIOURAL ATTITUDE OF ASHAs IN PRIMARY HEALTH CENTRES OF A COMMUNITY DEVELPOMENT BLOCK OF KANPUR NAGAR - Singh, Abhay; Saxena, S C; Srivastava, V K; Martolia, D S; Varma, Punit; Sharma, R P; Midha, Tanu (Indian Journal of Community Health, 2010)
Objective: 1. To assess the bio-social characteristics of ASHAs. 2. To analyse behavioural attitude of ASHAs. 3. To suggest measures j àr behavioural changes and further strengthen the NHRM programme implementation at grass-root level. Study Design : Cross sectional Study Period: March 2009- March 2010. Statistical Analysis : Percentage and Chi-square test. Methodology : All the J35ASHAs of randomly selected CDB Kalayanpur, Kanpur Nagar were studied by questionnaire method. Observations : Predominantly ASHAs belonged to age group of 30-35 years (45.2%), Hindu religion (99.3%), OBC caste (54.1%), educated upto 8 class (57.8%) and Social Class IV (68.9%). Amongst all the ASHAs, the behavioural attitude of majority of them (88.1%) was found communicative. Conclusions: In view of above observations, it is concluded that higher education level of ASHAs increases positive behavioural attitude other than their own temperament.